2019
DOI: 10.1111/lcrp.12159
|View full text |Cite
|
Sign up to set email alerts
|

Do exonerees face employment discrimination similar to actual offenders?

Abstract: PurposeGiven that criminal offenders face employment discrimination (Ahmed & Lang, 2017, IZA Journal of Labor Policy, 6) and wrongly convicted individuals are stereotyped similarly to offenders (Clow & Leach, 2015, Legal and Criminological Psychology, 20, 147), we tested the hypothesis that exonerees – despite their innocence – face employment discrimination comparable to actual offenders.MethodsExperienced hiring professionals (N = 82) evaluated a job application that was identical apart from the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…Moreover, Perreault et al (2017) found that social support-another key variable in the current study-mediated the relationship between full-time employment and depression. Unfortunately, however, many exonerees struggle to find employment due to limited job skills, résumé gaps, hiring discrimination, and/or difficulty having their wrongful conviction expunged (Chunias & Aufgang, 2008;Kukucka et al, 2020), such that providing job training via statute and/or preventing employers from asking about applicants' criminal history (i.e., "Ban the Box" policies; Maurer, 2019) stands to benefit exonerees' reentry in more ways than one.…”
Section: P Olicy Im Plicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Perreault et al (2017) found that social support-another key variable in the current study-mediated the relationship between full-time employment and depression. Unfortunately, however, many exonerees struggle to find employment due to limited job skills, résumé gaps, hiring discrimination, and/or difficulty having their wrongful conviction expunged (Chunias & Aufgang, 2008;Kukucka et al, 2020), such that providing job training via statute and/or preventing employers from asking about applicants' criminal history (i.e., "Ban the Box" policies; Maurer, 2019) stands to benefit exonerees' reentry in more ways than one.…”
Section: P Olicy Im Plicationsmentioning
confidence: 99%
“…Several studies have gauged public attitudes toward wrongly convicted individuals, generally finding that exonerees-despite their innocence-are negatively stereotyped and stigmatized similarly to actual offenders (e.g., Blandisi et al, 2015;Clow & Leach, 2015a;Thompson et al, 2012; for an exception, see Tudor-Owen et al, 2019; for a review, see Faison & Smalarz, 2019). Accordingly, field experiments have found that exonerees face employment discrimination (Clow, 2017;Kukucka et al, 2020) and housing discrimination (Kukucka et al, 2021;Zannella et al, 2020) comparable to offenders, which present considerable barriers to reintegration. To explain such findings, researchers have speculated that the public may doubt exonerees' innocence (perhaps to preserve their belief in a just world; Hafer & Bègue, 2005;Scherr et al, 2018a) and/or believe that exonerees have been corrupted by their prison experience (i.e., stigma-by-association; Clow et al, 2012;Goffman, 1963).…”
Section: Introductionmentioning
confidence: 99%
“…Exonerated offenders seeking a job to provide financial support may experience some of the same stigmatizing perceptions associated with ex-offenders. One study (Kukucka et al, 2020) even suggests that perceptions of exonerated individuals seeking employment may be more negative than those of former offenders. If the exoneration involved an offense for which there was a confession that was subsequently retracted-a "false confession"-that may increase the bias against exonerated individuals seeking work (Kukucka & Evelo, 2019).…”
Section: Financesmentioning
confidence: 99%
“…Tudor-Owen et al, 2019). It appears stronger toward Black exonerees under some circumstances (Howard, 2019;Scherr et al, 2018) and may adversely affect the likelihood of obtaining a job (Clow, 2017;Kukucka et al, 2020). Such stigma is likely to affect the post-incarceration functioning of exonerated individuals in various ways.…”
Section: Stigmamentioning
confidence: 99%
See 1 more Smart Citation